Three-dimensional Organization of Polytene Chromosomes in Somatic and Germline Tissues of Malaria Mosquitoes - George, Phillip (Cells, 2020)
Spatial organization of chromosome territories and interactions between interphase chromosomes themselves, as well as with the nuclear periphery, play important roles in epigenetic regulation of the genome function. However, the interplay between inter-chromosomal contacts and chromosome-nuclear envelope attachments in an organism’s development is not well-understood. To address this question, we conducted microscopic analyses of the three-dimensional chromosome organization in malaria mosquitoes. We employed multi-colored oligonucleotide painting probes, spaced 1 Mb apart along the euchromatin, to quantitatively study chromosome territories in larval salivary gland cells and adult ovarian nurse cells of Anopheles gambiae, An. coluzzii, and An. merus. We found that the X chromosome territory has a significantly smaller volume and is more compact than the autosomal arm territories. The number of inter-chromosomal, and the percentage of the chromosome–nuclear envelope, contacts were conserved among the species within the same cell type. However, the percentage of chromosome regions located at the nuclear periphery was typically higher, while the number of inter-chromosomal contacts was lower, in salivary gland cells than in ovarian nurse cells. The inverse correlation was considerably stronger for the autosomes. Consistent with previous theoretical arguments, our data indicate that, at the genome-wide level, there is an inverse relationship between chromosome-nuclear envelope attachments and chromosome–chromosome interactions, which is a key feature of the cell type-specific nuclear architecture.